Physicochemical Properties and Antioxidant Potential of Gels from Foam Mat Drying and Ethanolic Extract of Red Spinach (Amaranthus cruentus) - Arifin, Ibrahim; Anwar, Khoirul; Arsyada, Muhammad Farih; Pratiwi, Nevy; Shabrina, Ayu (Borneo Journal of Pharmacy, 2024)
Red spinach (Amaranthus cruentus), a rich source of antioxidant anthocyanins, is susceptible to light degradation. Foam mat drying (FMD) is a promising technique to preserve these pigments. This study compared the physicochemical properties and antioxidant activity of gels incorporating FMD and ethanolic extracts of A. cruentus (EEAC). Both were incorporated into gels at varying concentrations (1%, 3%, and 5%). FMD gels exhibited a darker red color and significantly higher total anthocyanin content (8.33 ± 0.25/100 g) and stronger antioxidant activity (IC50 of 35.67 ± 1.87 ppm) compared to EEAC gels (10.45 ± 0.15/100 g and IC50 of 47.88 ± 2.45 ppm, respectively). Both gel types had similar pH values (5.32-5.77). Increasing the concentration of either extract affected the viscosity, spreadability, and adhesion of the gels. Importantly, FMD gels displayed significantly higher antioxidant activity (58.75 ± 2.12 to 64.72 ± 2.01%) than EEAC gels (31.75 ± 2.13 to 50.12 ± 3.01%) across all formulations. These findings suggest that FMD-based gels offer a superior delivery system for A. cruentus antioxidants, potentially leading to innovative food products with enhanced nutritional value and health benefits.